Kynurenine metabolism in multiple sclerosis - Hartai Zsuzsanna (ACTA NEUROLOGICA SCANDINAVICA, 2005)
Objective - Excitatory amino acid receptors are involved in the normal physiology of the brain, and may play a role in the pathogenesis of neurological disorders such as Huntington's disease, Parkinson's disease, amyotrophic lateral sclerosis, etc. It has been demonstrated that the blockade of one of these receptors ameliorates the symptoms of experimental allergic encephalomyelitis, an animal model of multiple sclerosis (MS). In a recent study, a decreased level of kynurenic acid was found in the cerebrospinal fluid of patients with MS. The only known endogenous excitotoxin receptor antagonist is the tryptophan metabolite kynurenic acid. Another metabolite is quinolinic acid, which exerts different action: it is an excitotoxin receptor agonist. The ratio of these two metabolites is determined by the activities of kynurenine aminotransferase I and II (KAT I and KAT II). In this study, we measured the activities of these enzymes and the concentration of kynurenic acid in the red blood cells (RBC) and in the plasma of patients with MS. KAT activities were detected both in the RBC and in the plasma. As compared with the control subjects, the KAT I and KAT II activities were significantly higher in the RBC of the patients. The concentration of kynurenic acid is elevated in the plasma of MS patients, and there is a tendency to an elevation in the RBC. These changes may indicate a compensatory protective mechanism against excitatory neurotoxic effects. Our data demonstrate the involvement of the kynurenine system in the pathogenesis of MS, which may predict a novel therapeutic intervention.